Modality of Chinese Crossbreed Politicians in Local Democratization - Festianto, Dian; Usboko, Ignasius (Politika: Jurnal Ilmu Politik, 2021)
This research aimed at explaining the use of Chinese crossbreed politicians’ modality in the electoral political domain. This research uses the concept of modalities. The results showed that the utilization of Chinese crossbreed identity by politicians took place in three areas, namely the general public, the mass base, and political parties. The dualism of identity—the crossbreed between Indonesian Chinese descendants and Timorese-is a result of the giving of clans’ identity and intermarriage with local aristocrats, the dominating figures in the economic sector, and the holders of high positions in the elite ranks of political parties. The cross-identities were mobilized and turned out to be quite effective in the election of Chinese crossbreed politicians in the legislative body in the 2019 general election. This is inversely proportional to the Chinese crossbreed politicians women who have local maternal clans. The political practice shown by Chinese crossbreed politicians, on the one hand, strengthens identity politics but on the other hand, strengthens the political representation of minorities in the crossborder area of Indonesia and Timor Leste.